Efektivitas Karbon Aktif Dari Cangkang Biji Karet (Hevea Brasiliensis) Terhadap Kualitas Fisik Air Sumur Di Perumahan Kenten Laut - Melati Ireng Sari; Siti Chodijah (Journal of Innovative and Creativity, 2025)
South Sumatra has the largest rubber plantation area in Indonesia. Rubber seed shells (Hevea Brasiliensis) are one of the solid wastes produced from the plantation sector. This waste has various potentials, one of which can be used as activated carbon because it contains quite high cellulose, namely 48.64%. Activated carbon is made through three stages, namely dehydration, carbonization and activation using H3PO4. Activated carbon is used to determine the ability to adsorb pollutants in well water based on pH, Turbidity, and TDS parameters. The optimum dose of activated carbon used is 2 grams. This dose is able to improve the quality of well water so that it is below the quality standard, namely pH to 7.14, Turbidity to 2.65 NTU and TDS to 230 mg/ L.